Propuesta de mejora de procesos e implementación inicial de buenas prácticas de manufactura (bpm) y plan haccp en la planta de panadería "arenas" - Carrasco García, Karen Eliza (2014)
This work was done in the company Bakery and Biscuits “Arenas” CA, a company dedicated to the elaboration of bread, cakes and cookies, and for this he initial diagnosis of the company was conducted by using a checklist based on the 3253 Regulation of Good Manufacturing Practices for processed foods. With everything described above it was determined the company´s shortcomings according to the eight chapters established by this regulation, after this, the master plan and the manual of GMP (Good Manufacturing Practices) was performed. After implementation of the corrective actions a verification guide of GMP was performed to determine the percentage of improvement achieved. In the preliminary assessment was obtained 41 percent compliance, and after the initial deployment, it was reached 74 percent, indicating a substantial improvement of compliance with GMP standards…